Perencanaan Strategis Lembaga Amil Zakat Al-Kahfi Peduli dalam Meningkatkan Kualitas Daya Saing - Syafitri, Asri; Abidin, Yusuf Zaenal; Yaya, Yaya (Tadbir: Jurnal Manajemen Dakwah, 2022)
This research aims to know strategic intent, strategic mission, and strategic flexibility applied in the LAZ Al-Kahfi Peduli society’s in improving its competitiveness qualities. This type of research is qualitative with a descriptive approach. Data collection methods are regenerated by observation, interviews, and associated literature studies. Research shows that strategic planning has succesfully achieved prime Al-Kahfi Peduli’s competitiveness quality.